On aesthetic and cultural issues in pragmatic translation based on the translation of brand names and brand slogans - Feng, Xiuwen (China Perspectives series, 2017)
This book focuses on the cross-cultural advertising communication and aesthetic issues of brands and brand slogans. Based on the pragmatic translating theories and case studies of a few classic brand translations, the book puts forward the Three Aesthetic Principles of translating brands.